Game Space and Game Situation as Mediators of the External Load in the Tasks of School Handball - Feu, Sebastián; Garcia-Ceberino, Juan Manuel; Gracia Gamero, Maria; Gonzalez-Espinosa, Sergio; Antunez, Antonio (International Journal of Environmental Research and Public Health, 2023)
The teacher's didactic intervention also requires knowledge and control of learning tasks' workloads. The objectives of the study were as follows: (i) to quantify the subjective external load-eTL of tasks framed in didactic units designed by in-service teachers; and (ii) to analyze the differences in the subjective eTL according to the game situation and the game space. A total of 306 learning tasks designed by seven in-service teachers (five men and two women), with more than 10 years of teaching practice, were analyzed. These tasks were coded through the Integral System for Training Task Analysis (SIATE, acronym in Spanish). The interobserver reliability of the coded variables obtained a considerable concordance (MKfree > 0.70). The results indicated that there were significant differences in the subjective eTL according to the game situation and game space. The situations of small-sided games in numerical equality or inequality and full games, in medium spaces or large spaces, presented a higher subjective eTL and therefore the highest physiological and motor demands on students. The inclusion of attacking or defending players and an adequate selection of the game space indicated the importance of planning and organizing learning tasks.
Keywords: planning; external load; service teachers; SIATE; Scopus; JCR